IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH PROJECT BASED LEARNING (A Classroom Action Research in the Second Year of MTs Jamiyyah Islamiyyah Pondok Aren) - Yuliana Friska (IAIN Syekh Nurjati Cirebon, 2018)
The aim of this study is to know whether students’ reading comprehension of narrative text could be improved by applying Project Based Learning in the second year of MTs Jamiyyah Islamiyyah Pondok Aren academic year 2015/2016. This study is categorized as the Classroom Action Research (CAR) method in which to identify and to solve the problem on students’ reading comprehension. It is initiated through the interview the teacher and through the observation in the VIII grade class VIII.5 at MTs Jamiyyah Islamiyyah Pondok Aren; considered as the class whose reading test score are very low. The amount of students in that class is 36. In this Classroom Action Research, the writer implements the Kurt Lewin’s design which consists of four phases. Therefore, this study is included into quantitative descriptive research. The findings of this study are: (1) related to the test result, there was 20.28% improvement of students’ mean reading score after using Project Based Learning; it gained from the pretest result, there were two students who passed the KKM. Then in the result of posttest in cycle 1, there were 11 or 31% students in the class who passed the KKM considering their mean score of the test is 62.78. Next in the result of posttest in the cycle 2, there were 30 or 83% students who passed the KKM in which their mean score of reading test derived 73.19. (2) Related to the observation result showed that the students were more active and interested in reading activity in the classroom. Indeed, they were able to analyze the text and to get information from the text well. (3) Related to the interview result, it could be known that the students’ reading comprehension in term of narrative text has improved and also assisted the teacher in finding the appropriate strategy in teaching reading especially narrative text.